(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the effect of bench curing on bond strength of denture base with acrylic teeth. Study Design: An experimental, in-vitro study. Place and Duration of Study: This study was conducted at the Sir Syed College of Medical Sciences (dental section) for Girls and Dow Dental College, Dow University of Health Sciences, Karachi from February 2023 till March 2023. Materials and Methods: Forty specimens were fabricated according to standards of ADA No. 15. These specimens were divided into 4 groups as per bench curing time. In Group 1 specimens were not bench cured and were directly put in curing tank for processing. In Group 2 specimens were bench cured for 30 minutes, in Group 3 for 1 hour and in Group 4 for 2 hours. Processing in curing tank was carried out at 73°C for 90 minutes followed by 100°C for 30 minutes. Tensile load was applied at the junction of denture base and acrylic teeth. Analysis of data was done through SPSS software 21. Statistical significance was assessed by applying one way ANOVA and post hoc Tukey test. Cohesive, adhesive and mixed type of failure was assessed with naked eye. P-value less than 0.05 was considered as statistically significant. Results: No statistical significant difference was found between any of the groups (p>0.05). Tensile load value observed in newton was highest for group 3 but there was no statistical significant difference (p>0.05). None of the groups showed cohesive failure above 80%. Conclusion: Processing of denture base with or without bench curing did not affect strength of bond between denture base and acrylic teeth.